STATE OF PROBLEMS OF SELF-CONTROL OF STUDENTS 'EDUCATIONAL ACTIVITIES IN SCIENTIFIC AND PEDAGOGICAL LITERATURE - M.N. Moskalets (Academy of Cognitive and Natural Sciences, 2009)
In the article was considered theme of pedagogical control and self control of students of higher educational establishments with description of different constituents in the process of forming of awareness students them educational activity.